The Impact of Integrated Business Communications on the Success of Enterprises and Organizations - A. V. Lopukhin; E. A. Plaksenkov (Мир новой экономики, 2024)
This paper evaluates the impact of business communications on the performance of companies and organizations and briefly outlines the history of the formation of the conceptual apparatus in the process of integrating integrated communications. Their role in corporate governance, as well as in the implementation of the ESG agenda in Russia, is considered. The relevance of the study is determined by the accelerated changes in the concepts of communication integration, the constant updating of forms, methods, tools and technologies, as well as the ambiguity of interpretations and the insufficient development of methodological approaches, which requires a new understanding of their content and implementation possibilities. The similarities and differences between integrated marketing communications and integrated communications are analyzed, the uncertainty in the use of these concepts is shown, as well as the distinctive features of the latter, which interact with all groups of stakeholders. The subject of the study is the system of relations in the process of interaction of companies and organizations with all groups of stakeholders. The purpose of the article is to show the advantages and possibilities of practical application of integrated communications, as well as new approaches to management strategizing. The article uses such research methods as content analysis of scientific periodicals, comparative analysis of semantic constructions of terms, study of practical experience in managing communications of companies and organizations, criteria and indicators for assessing their quality. The current trends in the development of integrated communications and their growing influence on the performance of companies and organizations are shown. The scientific novelty of the publication is justified by the author’s interpretation of the process of communication integration. The analysis showed that in the methods for compiling ESG ratings, the set of criteria for assessing the quality of block “G” is limited to the indicators of corporate governance codes. Therefore, the authors propose to expand this set using metrics for assessing the effectiveness of integrated communications management taken from the “corporate management” and “communications management” systems. The practical significance of the work is the opportunity to attract the attention of stakeholders to the problem of integrated communications and expand the horizon of their perception in theory and practice. Further directions of research may be related to the consideration of the characteristics of Russian communications practices in the business environment. Effective integrated communications can play a key role in the development of sustainable corporate governance in Russia.